2015
DOI: 10.4149/av_2015_03_221
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits bovine herpesvirus type 1 entry into MDBK cells

Abstract: Summary. -The generation of antiviral drugs from herbs and other natural resources with traditionally longconfirmed effects is an efficient approach. So far, no herb or components from herbs that could inhibit bovine herpesvirus type 1 (BoHV-1) replication have been described. In this study, the antiviral effect of curcumin, a natural phenolic constituent of the spice turmeric, on BoHV-1 replication was evaluated in cell culture. We demonstrated that curcumin impairs BoHV-1 viral particles and affects the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Bovine herpesvirus 1 (BoHV-1) incubated directly with 10 µM of curcumin caused a significant reduction in viral titer as analyzed by TCID 50 [23]. However, curcumin did not reduce BoHV-1 titer during a binding assay, suggesting curcumin does not prevent viral attachment but, rather, may be affecting internalization.…”
Section: Bovine Herpesvirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine herpesvirus 1 (BoHV-1) incubated directly with 10 µM of curcumin caused a significant reduction in viral titer as analyzed by TCID 50 [23]. However, curcumin did not reduce BoHV-1 titer during a binding assay, suggesting curcumin does not prevent viral attachment but, rather, may be affecting internalization.…”
Section: Bovine Herpesvirusmentioning
confidence: 99%
“…In Madin-Darby Bovine Kidney (MDBK) cells, 10 µM of curcumin significantly reduced viral titer when applied at the time of infection, but it had no significant effect when added immediately after the one h incubation of cells with the virus inoculum. The authors speculate that curcumin may be inhibiting BoHV-1 infection by upregulating lipid raft formation, a process they previously reported to be disrupted during BoHV-1 infection [23,77]. Reolon et al [78] evaluated the co-encapsulation of acyclovir, an approved pro-drug that inhibits HSV replication [79], and curcumin into three microparticle (MP) formulations composed of the polymers hydroxypropyl methylcellulose, Eudragit ® RS100, or both for efficacy against BoHV-1.…”
Section: Bovine Herpesvirusmentioning
confidence: 99%
“…Curcumin has a polyphenol structure and has been traditionally used as a household treatment for various diseases 12 . Several studies suggested that curcumin has antimicrobial, 13 anti-inflammatory, 14 antioxidant,15, 16 immunomodulatory, 17 renoprotective, 18 anti-cancer, 19 hepatoprotective, 20 phypoglycaemic 21 properties which are acts through signaling pathways and regulating gene expression 22 …”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is effective in the management of virus infections as it inhibited Zika and Chikungunya virus at a concentration of 5 μM (IC50 = 1.9 and 3.89 μM respectively) [31], herpes simplex virus [32] and dengue virus [33]. Further, it inhibited human immunodeficiency virus (HIV) integrase and protease suggesting its protective effects against AIDS [34,35].…”
Section: Turmericmentioning
confidence: 99%